SEKTOR BARU PENGELOLAAN SAMPAH DI INDONESIA (STUDI KASUS DI KOTA YOGYAKARTA, KABUPATEN SLEMAN DAN BANTUL) - Hijrah Purnama Putra; Enri Damanhuri; Emenda Sembiring (Teknik Lingkungan Universitas Islam Indonesia, 2019)
The rate of municipal waste generation increases along with the increase in population, infrastructure and supporting activities in it. But in developing countries, the amount of waste is not comparable with the government's performance in handling it. The role of the government in waste management, in this study is referred to as the formal sector. Various limitations arise in this formal sector, such as minimal funding, human resources and the availability of infrastructure. In addition to the formal sector, there are also informal activities that play a role, but the motives for their activities are not environmental issue, but economic motives for individuals and groups, so that their large role is not considered in municipal solidwaste management and planning. The Indonesian government presents other sectors in the Solidwaste Bank and TPS 3R programs, this sector is referred to as the semi-formal sector, because of the government's involvement but operated by the community. The motive is also integrated between environment and economy as a step of empowerment. This study aims to present the semi-formal sector, whose task is to assist in the handling and reduction of waste at both at the source and the larger scale (comunal), as a new sector in the solidwaste management system in Indonesia. Keywords : Semi-formal sector, Solidwaste Bank, Solidwaste management, TPS3R